Pendampingan peningkatan profesionalitas guru Bahasa Indonesia melalui literasi menulis artikel di jurnal ilmiah - Muhlis Fajar Wicaksana; Suparmin Suparmin; Titik Sudiatmi; Sri Muryati (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2021)
Teachers are currently required to produce scientific works, especially writing scientific articles. The purpose of this community service is to improve teacher professionalism literacy in writing scientific articles. The method applied in community service activities is descriptive qualitative through training and mentoring activities intended for teachers of the Indonesian Language Senior High School Subject Teacher Consultation (MGMP) in Sukoharjo. The implementation method in community service is carried out through the following stages: 1) preparation (observations and action plans); 2) implementation; 3) evaluation and feedback; 4) assistance in compiling scientific articles. The results of this training include a positive response from the trainees and an increase in the skills of teachers in literacy in writing scientific articles. The final results showed that of the 30 participants who participated in the mentoring, there were ten manuscripts of scientific articles for Indonesian language teachers in Sukoharjo adapted to the scientific journal templates to be addressed. The journals targeted include Klitika Journal; Scientific Journal of Indonesian Language and Literature Education, Univet Bantara; Literature Journal; Journal of Language Education and Teaching Sebelas Maret University; TABASA Journal; Indonesian Language Tadris Scientific Journal IAIN Surakarta; and the Linguistic Journal; PGRI Madiun University. If a percentage of 33% of participants succeeded in submitting in achieving the goal of publishing in the desired scientific journal, as many as 45% succeeded in converting the PTK report into articles, the remaining 22% were still struggling with revisions of converting reports into articles. It can be concluded that, in total, 78% of the total number has shown maximum progress in the mentoring process.